2008
DOI: 10.1007/s10552-008-9278-7
|View full text |Cite
|
Sign up to set email alerts
|

Number of aberrant crypt foci associated with adiposity and IGF1 bioavailability

Abstract: Background Dysregulation of the insulin-like growth factor (IGF) system, a common consequence of adiposity-induced insulin resistance, may be a key underlying mechanism linking excess body weight with colon cancer. Evidence has been derived from studies of cancer and polyps. Supporting data about aberrant crypt foci (ACF), putative pre-polyp changes, have been generated only from animal studies to date. Methods We randomly selected 26 patients with sex-specific elevated waist-hip-ratio (WHR) and 26 with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Additionally, Swede et al showed increased BMI to be associated with increased number of prevalent ACF 4. Our result here, of a modest, but not statistically significantly elevated risk for recurrent ACF in obese subjects (OR=1.4) seems more in line with the literature than our earlier finding from the baseline exam.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, Swede et al showed increased BMI to be associated with increased number of prevalent ACF 4. Our result here, of a modest, but not statistically significantly elevated risk for recurrent ACF in obese subjects (OR=1.4) seems more in line with the literature than our earlier finding from the baseline exam.…”
Section: Discussionsupporting
confidence: 91%
“…But there is considerable evidence that insulin and IGF-IR are important growth factors for gastrointestinal tissue and provide protection to several cell types, including colon cancer cells [21,22]. The presence of elevated insulin, IGF-IR, and TNF-α could act synergistically to provide superior survival and growth conditions to developing preneoplastic lesions and tumors [18,23,24]. Moreover, inhibition of NF-κB and MAPK is crucial for Bars not sharing a common superscript are significantly different, p<0.05, as determined by ANOVA analyses with LSD and Tukey post hoc tests reversing the survival signal mediated via IGF, as well as TNF-α [21].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently these patients returned for a surveillance exam at UCHC for indications of a prior history of adenoma (n = 48) or family history of colon cancer (n = 26). The structure and methodology of the ACF Study have been described in detail elsewhere [9,10,13]. Briefly, the ACF Study is a clinic-based research program with a goal to characterize the clinical importance, epidemiologic risk factors for and molecular features of ACF and other early colonic neoplasia, which was approved by the UCHC Institutional Review Board.…”
Section: Patient Population and Study Designmentioning
confidence: 99%
“…Colon preparation prior to the procedure is performed with polyethylene glycolbased liquid as described in our prior reports [9,10]. ACF detection took place after the standard colonoscopy was completed.…”
Section: Acf Detectionmentioning
confidence: 99%
See 1 more Smart Citation